The use of information technology by restaurants in Joglosemar, the mainstay city of Indonesian culinary - Andi Asrihapsari; Doddy Setiawan (Jurnal Manajemen dan Pemasaran Jasa, 2020)
According to the Indonesian Ministry of Tourism, Yogyakarta, Surakarta, Semarang (Joglosemar) are top culinary destinations in Indonesia, with information technology (IT) needed to strengthen its development. Therefore, this study examines IT's adaptation in restaurants owned by micro, small, and medium enterprises (MSMEs) at Joglosemar. This is a descriptive research with data obtained from 200 restaurants each in three cities through questionnaires, interviews, and observation, culminating in 600 restaurants. The result showed that restaurants adopt IT contact (92%), online transportation partner (81%), non-cash cashier payment (66%), IT cashier (61%), Wi-Fi (57%), and large orders-outside restaurant (49%) to improve their performance. This research contributes to providing a current overview of the development of IT restaurants in Indonesia, therefore it is expected to enable the entrepreneur to be more ready to face the business competition in the digital era. This research is limited to Joglosemar, therefore further study needs to investigate other top culinary cities. Secondly, this is a descriptive research on the adoption of IT by restaurants in Joglosemar, therefore further study needs to elaborate on the determinants factors of adoption of IT by restaurants and its effects on performance.